Prevalence Of Obesity Among College Students in Rural Area of Bangalore - Sanjay T Varadappa; Prashanth Kumar S Prakash; Gangaboraiah; Ramesh Masthi N Raju; Lakshmeesha Y Subbanna (Medsci Publications, 2014)
Introduction: Increasing trend of obesity among adolescents is a worldwide phenomenon. There is a scarcity of research on obesity in the later part of adolescence from rural part of India. Objective: To find out the prevalence and factors associated with obesity among college students studying 11th& 12th standard between 15 - 19 years of age. Methods: A cross sectional study was undertaken by involving all the colleges located within the rural field practice area of Kempegowda Institute of Medical Sciences, Bangalore for a period of 6 months (Apr - Sep 2009).The data was collected from students (n=1170) using pre-tested structured questionnaires. Anthropometric measurements such as height, weight, waist circumference and body fat percentage were taken for all the students. The criteria for overweight/obesity and central obesity were based on proposed WHO Asia-Pacific guidelines and International Diabetes Federation (IDF) guidelines. Results: Overweight/ obesity were found to be 6.1% and 7.2% respectively and central obesity of 1.9%.The overweight/obesity had significant association with age and family history of obesity. The mean BFP was significantly higher among boys in the age group of 15-16 years compared to 17-19 years age group and significant difference in the mean BFP was noted among both boys and girls with family history of obesity. The mean body fat percentage was significantly high in overweight/obesity and central obesity. Conclusions: The present research has found prevalence of overweight/obesity of 13.3% and central obesity of 1.9% respectively in the age group of 15-19 years, which needs to be confirmed in future studies.